If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -4) + -5 = -2 Reorder the terms: 3(-4 + y) + -5 = -2 (-4 * 3 + y * 3) + -5 = -2 (-12 + 3y) + -5 = -2 Reorder the terms: -12 + -5 + 3y = -2 Combine like terms: -12 + -5 = -17 -17 + 3y = -2 Solving -17 + 3y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 3y = -2 + 17 Combine like terms: -17 + 17 = 0 0 + 3y = -2 + 17 3y = -2 + 17 Combine like terms: -2 + 17 = 15 3y = 15 Divide each side by '3'. y = 5 Simplifying y = 5
| 7(2+5)=x | | x(6)+y(y)=24 | | n-2+n+2=0 | | 4(y+3)=48 | | 3x+2(x-9)=8x+x-14 | | -10-3x=-10 | | 80(x-8)=48(x+8) | | 4=h+2 | | 6=5p-5-4p | | 4z^2+5z-6=0 | | 7x+2y=23 | | 5x+10-8=4x-2 | | -3y+3y+4=4 | | -6=2+b | | 4x+4=3x-2 | | 6(h+1.5)-1=4h-8 | | -1=-4(b-2) | | 28x-7=5x+11 | | 4(2x+14)=0 | | 6x-5=3x-1 | | 2x+9=5+4x | | -4a+12a-3a= | | -3(x+5)=3(7+3t) | | 3a-14=61 | | 6a^5+37a^3b^2+6ab^4=0 | | x+y+z=410 | | 12x^3y+10x^2y-8xy=0 | | 7y+3=80 | | 2(-3x-6)=3(2x-4) | | 4x+y=410 | | 57-9=8m | | x/3.7=6 |